2012
DOI: 10.1088/0741-3335/55/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of drift-wave turbulence and transport in a stellarator

Abstract: Abstract. The three-dimensional structure of drift-wave turbulence and turbulent transport is investigated in plasmas of the stellarator experiment TJ-K. By means of two poloidal Langmuir probe arrays placed at different toroidal positions, density and potential fluctuations are recorded simultaneously at 128 positions on a single flux surface. From this data, the spatial drift-wave turbulence pattern including perpendicular and parallel structure sizes are obtained using a cross-correlation technique. A compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 58 publications
5
24
0
Order By: Relevance
“…In this region the normal curvature is still negative whereas the geodesic curvature is positive. A similar behaviour has been found for the radial cross-field transport G = á ñ   v n r [25,34]. These investigations have shown that the turbulent transport is peaked in regions with the above mentioned combination of curvature parameters (k < 0 n , k > 0 g ).…”
Section: Poloidal Dependence Of Background Reynolds Stresssupporting
confidence: 80%
See 2 more Smart Citations
“…In this region the normal curvature is still negative whereas the geodesic curvature is positive. A similar behaviour has been found for the radial cross-field transport G = á ñ   v n r [25,34]. These investigations have shown that the turbulent transport is peaked in regions with the above mentioned combination of curvature parameters (k < 0 n , k > 0 g ).…”
Section: Poloidal Dependence Of Background Reynolds Stresssupporting
confidence: 80%
“…Although the plasma parameters are comparatively low, it has been shown that normalised quantities are similar to those in fusion edge plasmas [20,21]. Furthermore, many studies demonstrated the drift-wave nature of the plasma turbulence in the TJ-Kdevice with a density-potential cross phase close to zero and finite parallel wavelength [22][23][24][25]. Especially for small ion masses the r s scaling was found to be close to predictions for drift-wave turbulence [26].…”
Section: Global Reynolds Stress Measurementmentioning
confidence: 73%
See 1 more Smart Citation
“…The decrease of the difference in α towards the core could be due to an increase in parallel correlation length according to equation 16. A parallel correlation length of 2 m would be rather small compared to result from previous studies [14,15,16,17](but not impossible).…”
Section: Comparison With the Cliste Code At Augmentioning
confidence: 64%
“…Investigations of turbulent drift waves have been stimulated by their importance for anomalous transport in magnetized plasmas and fusion plasma experiments in particular (Liewer, 1985;Wootton et al, 1990;Misguich et al, 1987;Horton, 1990Horton, , 1999. The present summary implicitly assumes locally homogeneous magnetic fields, but drift wave turbulence has been observed in more complex magnetic field configurations such as stellarators (Bol, 1964;Birkenmeier et al, 2013).…”
Section: Strong-versus Weak-turbulence Modelsmentioning
confidence: 92%